1997
DOI: 10.1007/s001250050646
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of pramlintide, a human amylin analogue, delays gastric emptying in men with IDDM

Abstract: Pramlintide, a human amylin analogue, reduces hyperglycaemia after meals in patients with insulin-dependent diabetes mellitus (IDDM). We investigated whether this was due to delayed gastric emptying. Eight men with uncomplicated IDDM were studied twice in a randomised, double-blind crossover design. Euglycaemia was maintained overnight by intravenous infusion of glucose and/or insulin and the following morning a 5-h infusion of pramlintide 25 micrograms/h or placebo was started at 08.00 hours. At 08.30 hours t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 25 publications
4
92
0
Order By: Relevance
“…This could possibly be due to a delay of emptying caused by endogenous amylin and/or insulin which will have been co-secreted in response to the glucose drink. Thus, subcutaneous injections of pramlintide cause retention of food in the proximal stomach, similar to an intravenous infusion of pramlintide [10]. This may be an extension of the effects of glucose described by Collins et al [22].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This could possibly be due to a delay of emptying caused by endogenous amylin and/or insulin which will have been co-secreted in response to the glucose drink. Thus, subcutaneous injections of pramlintide cause retention of food in the proximal stomach, similar to an intravenous infusion of pramlintide [10]. This may be an extension of the effects of glucose described by Collins et al [22].…”
Section: Discussionmentioning
confidence: 67%
“…In a previous study we have shown that an intravenous infusion of pramlintide delayed gastric emptying in men with IDDM but the dose of pramlintide was supraphysiological in relation to the amylin response to food in non-diabetic subjects [10]. The purpose of this study was to examine the dose response effect of pramlintide on gastric emptying and to determine the duration of any effect by assessing whether administration of the drug before one meal has an impact on the subsequent meal.…”
Section: : 577±583]mentioning
confidence: 99%
“…Amylin is a 37-amino acid polypeptide co-secreted with insulin 11 . In humans, exogenous administration of amylin and the amylin analogue, pramlintide, slows gastric emptying substantially 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, exogenous administration of amylin and the amylin analogue, pramlintide, slows gastric emptying substantially 11 . Furthermore, at least in animal models, amylin appears to be a more potent physiological regulator of gastric emptying than other enterogastrones, including CCK and glucagon-like peptide-1 (GLP-1) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Relative to insulin therapy alone, single-dose pramlintide supplementation represses postprandial glucagon secretion in T1D subjects , Heptulla et al 2005, Chase et al 2009, Hassan & Heptulla 2009). Furthermore, pramlintide administration delays gastric emptying of both solids and liquids in T1D subjects (Kong et al 1997, Vella et al 2002, Woerle et al 2008, Chase et al 2009). In fact, IAPP deficiency may contribute to the accelerated gastric emptying observed in uncomplicated T1D (Vinik et al 2008, Woerle et al 2008.…”
Section: Iapp Replacement In Type 1 Diabetesmentioning
confidence: 99%